An overview and analysis of telecom industries media expenditure (Jan'15- Jun'15) comparison with Robi Axiata Ltd. - Tripti, Jakia Afsana (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.